1998
DOI: 10.1002/(sici)1098-2752(1998)18:2<90::aid-micr6>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Drug-induced vasodilation: In vitro and in vivo study on the effects of lidocaine and papaverine on rabbit carotid artery

Abstract: Flap ischemia is often encountered during pedicled and free tissue transfer. In this study, the vascular effects of varying doses of lidocaine, papaverine, and a combination of the two agents were evaluated and compared in an in vitro and in vivo model in the rabbit carotid artery. In the in vitro study, 14 rings from the rabbit carotid artery were bathed in Krebs-Ringers solution and stretched progressively to an optimal tension of 3.7-4.2 grams. Their isometric contractile activity was measured. The specimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 27 publications
0
7
0
2
Order By: Relevance
“…17-19, 31, 32, 43 It has also been shown that lidocaine has a local spasmolytic effect in blood vessels when administrated topically, thereby improving blood flow. 44 Lidocaine has been proposed to act through several mechanisms, including a Na + /Ca 2+ pump blocker (sodium/calcium exchange protein), superoxide and hydroxyl radicals scavenger, inflammatory modulator and potent granulocyte, and endothelial cell function inhibitor. 17-19, 31, 32, 43 In our previous retrospective study of GDV, lidocaine, administered only at CRI at 0.05 mg/kg/min, failed to show any beneficial effects.…”
Section: Discussionmentioning
confidence: 99%
“…17-19, 31, 32, 43 It has also been shown that lidocaine has a local spasmolytic effect in blood vessels when administrated topically, thereby improving blood flow. 44 Lidocaine has been proposed to act through several mechanisms, including a Na + /Ca 2+ pump blocker (sodium/calcium exchange protein), superoxide and hydroxyl radicals scavenger, inflammatory modulator and potent granulocyte, and endothelial cell function inhibitor. 17-19, 31, 32, 43 In our previous retrospective study of GDV, lidocaine, administered only at CRI at 0.05 mg/kg/min, failed to show any beneficial effects.…”
Section: Discussionmentioning
confidence: 99%
“…10 In a subsequent report, the same authors reported that higher concentrations of lidocaine (20%) produced vasodilation similar to that of papaverine in rabbit carotid arteries. 19 Other groups have similarly reported dose-dependent vasoconstriction caused by lidocaine. 20,21 Lidocaine doses of 20% may lead to unwanted systemic toxicity, while lidocaine 2% may lead to vasoconstriction.…”
Section: Discussionmentioning
confidence: 95%
“…In experimental works, its topic use decreased the function of the myofibroblasts and improved circulation 39 . Papaverine also increases the blood flow of microvascular anastomosis 40,41 . However, no significant effect was found among the groups with or without the addition of papaverine, either in 14 or 28 days.…”
Section: Discussionmentioning
confidence: 99%